2013
DOI: 10.1161/strokeaha.111.678565
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Delay of Carotid Endarterectomy in Acute Ischemic Stroke Patients

Abstract: This nationwide study was based on data covering the entire Danish population (≈5.5 million). The National Health Service provides taxsupported health care to all residents, including free access to hospitals. Each resident holds a unique 10-digit civil registration number that is used in all Danish registries and enables unambiguous linkage between the registries. 13 The study was based on individual patient-level recordBackground and Purpose-Guidelines recommend carotid endarterectomy (CEA) within 2 weeks fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
2
8
0
1
Order By: Relevance
“…However, the median time to surgery was only approaching the national guideline of 14 days in 2010 (16 days), and meeting the guideline in 2014 (8 days). This lag has also been demonstrated in other studies conducted internationally …”
Section: Discussionsupporting
confidence: 81%
“…However, the median time to surgery was only approaching the national guideline of 14 days in 2010 (16 days), and meeting the guideline in 2014 (8 days). This lag has also been demonstrated in other studies conducted internationally …”
Section: Discussionsupporting
confidence: 81%
“… 44 A Danish nationwide initiative was able to increase the percentage of CEA within the recommended timeframe from 13% in 2007 to 47% in 2010. 45 The evidence of the early procedure safeness is more robust for CEA than for CAS which has conflicting results in different studies. 46 - 48 …”
Section: Resultsmentioning
confidence: 99%
“…The impact of the Danish National Indicator Project, launched in 2008, has been investigated in a Danish nationwide survey which showed that from 2007 to 2010, the percentage of patients with stroke and ICA stenosis who underwent CEA within 2 weeks increased from 13% to 47% (Witt et al, 2013). In the years before this study, our vascular department (Rathenborg et al, 2008) and others (Noronen et al, 2012) reduced the time from referral to surgery by introducing an accelerated course of examinationsa so-called fast track.…”
Section: Discussionmentioning
confidence: 99%